Genetic resource conservation of mediterranean oaks in Spain - Jiménez, P.; Gil, L. (Forest Systems, 2000)
Ecological and economical interest of mediterranean species of genus Quercus (Quercus ilex, Q. suber, Q. coccifera) justify the studies and actions focused on conservation of their genetic resources. As an essential basis for the development of conservation strategies, a review of the state of knowledge on these species diversity is offered, mainly referred to genetic variation. Factors determining genetic structure are commented, as well as the relevance of some marginal populations for conservation purposes. In spite of the peculiarities of each species, similar distribution and management lead to common conservation problems. Main threats come from the exploitation models: lack of regeneration, low maturity in coppices, uncontrolled seed movements, etc. Marginal populations have higher risk of disappearance due to their singular characteristics (low demographic size, limitant habitats). These menaces require the adoption of strategies in which the management promote natural regeneration and the evolution of the stands, while at the same time particular risks of each population are considered.